The Status of GDP Compilation Practices in 189 Economies and the Relevance for Policy Analysis - Berry, Francien (IMF Working Papers; Working Paper, 2018)
This paper examines the status of GDP compilation in 189 economies against six key criteria that describe national accounts compilation practices: whether the benchmark year is up to date, the availability and timeliness of annual and quarterly GDP, whether GDP by production and expenditure approaches are compiled independently to allow for comparisons, whether estimates by the income approach are available, and the vintage of the System of National Accounts (SNA) applied. We used publicly available information including from the IMF's Dissemination Standards Bulletin Board (DSBB), and, for 108 developing economies, information provided by the IMF's real sector advisors stationed in the Fund's 10 Regional Technical Assistance Centers (RTACs). The data were compared with the UNSD and World Bank databases. We find that 50 percent of economies have acceptable benchmark years, 72 percent report timely annual GDP data, while 55 percent of economies report timely data for quarterly GDP. The study presents some conclusions for priorities of capacity development.